Effectiveness of intermittent fasting on biochemical and anthropometric markers in obese adults with cardiovascular risk. A systematic review: Efectividad del ayuno intermitente sobre marcadores bioquímicos y antropométricos en adultos obesos con riesgo cardiovascular. Una revisión sistemática. - López-Espinoza, Miguel Á. (2022)
Background. Obesity is a problem present in almost all societies, which has led to the search for different methods to combat it. One of them is intermittent fasting (IF), characterized by periods without eating (16 to 24 hours), limited or no caloric intake, combined with normal eating windows. Target. To determine the effectiveness of intermittent fasting on biochemical and anthropometric markers in obese adults. Materials and methods. A systematic review was proposed that postulated to study blinded or open clinical trials of IA interventions, compared with a control group. The response variables were: systolic and diastolic blood pressure, total cholesterol, LDL, HDL and triglycerides, blood glucose, fat mass, weight, waist circumference, BMI and heart rate. The search and identification of studies was masked. The risks of bias for the Cochrane collaboration were assessed. They underwent meta-analysis (random effect), with R 4.0.0. Results. Six studies were included, involving 10-48 weeks of intervention with alternate-day fasting and time-restricted feeding, reporting some statistically significant changes for different variables. Conclusion. Intermittent fasting could intervene in the reduction of cardiovascular risk due to improvement in BMI and biochemical parameters.